A disposable OSL dosimeter for in vivo measurement of rectum dose during brachytherapy. Issue 8 (30th July 2021) - Hayashi, Hiroaki; Kimoto, Natsumi; Maeda, Tatsuya; Tomita, Emi; Asahara, Takashi; Goto, Sota; Kanazawa, Yuki; Shitakubo, Yasufumi; Sakuragawa, Kanako; Ikushima, Hitoshi; Okazaki, Tohru; Hashizume, Takuya
Abstract : Purpose: We aimed to develop a disposable rectum dosimeter and to demonstrate its ability to measure exposure dose to the rectum during brachytherapy for cervical cancer treatment using high‐dose rate 192 Ir. Our rectum dosimeter measures the dose with an optically stimulated luminescence (OSL) sheet which was furled to a catheter. The catheter we used is 6 mm in diameter; therefore, it is much less invasive than other rectum dosimeters. The rectum dosimeter developed in this study has the characteristics of being inexpensive and disposable. It is also an easy‐to‐use detector that can be individually sterilized, making it suitable for clinical use. Methods: To obtain a dose calibration curve, phantom experiments were performed. Irradiation was performed using a cubical acrylic phantom, and the response of the OSL dosimeter was calibrated with the calculation value predicted by the treatment planning system (TPS). Additionally, the dependence of catheter angle on the dosimeter position and repeatability were evaluated. We also measured the absorbed dose to the rectum of patients who were undergoing brachytherapy for cervical cancer ( n  = 64). The doses measured with our dosimeters were compared with the doses calculated by the TPS. In order to examine the causes of large differences between measured and planned doses, we classified the data into common and specific cases when performing this clinical study. For specific cases, the following three categories were considered: (a) patient movement, (b) gas in the vagina and/or rectum, and (c) artifacts in the X‐ray image caused by applicators. Results: A dose calibration curve was obtained in the range of 0.1 Gy–10.0 Gy. From the evaluation of the dependence of catheter angle on the dosimeter position and repeatability, we determined that our dosimeter can measure rectum dose with an accuracy of 3.1% (k = 1). In this clinical study, we succeeded in measuring actual doses using our rectum dosimeter. We found that the deviation of the measured dose from the planned dose was derived to be 12.7% (k = 1); this result shows that the clinical study included large elements of uncertainty. The discrepancies were found to be due to patient motion during treatment, applicator movement after planning images were taken, and artifacts in the planning images. Conclusions: We present the idea that a minimally invasive rectum dosimeter can be fabricated using an OSL sheet. Our clinical study demonstrates that a rectum dosimeter made from an OSL sheet has sufficient ability to evaluate rectum dose. Using this dosimeter, valuable information concerning organs at risk can be obtained during brachytherapy.